2019
DOI: 10.1111/clr.13455
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation on dental implants with different surface micro‐topography: An in vitro study

Abstract: Objectives:To compare biofilm formation on whole dental titanium implants with different surface micro-topography. Methods:A multispecies in vitro biofilm model consisting of initial (Streptococcus oralis and Actinomyces naeslundii), early (Veillonella parvula), secondary (Fusobacterium nucleatum) and late colonizers (Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans) was grown for 96 hr on sterile titanium dental implants with either minimal (S a : 0.5-1.0 mm) or moderate-roughness titanium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
3
34
0
1
Order By: Relevance
“…Several studies demonstrated that the bacterial coating on titanium surface was roughness-dependent and its adhesion to the rougher SLA surface was signicantly higher than the smooth surface. 32,33 In addition, as mentioned above, LPS and VSCs released form P. gingivalis could potentially promote titanium corrosion. 16 Thus, the higher degree of bacterial attachment, as well as the enhanced corrosion, may lead to more changes on the SLA titanium surface, including roughness and wettability.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies demonstrated that the bacterial coating on titanium surface was roughness-dependent and its adhesion to the rougher SLA surface was signicantly higher than the smooth surface. 32,33 In addition, as mentioned above, LPS and VSCs released form P. gingivalis could potentially promote titanium corrosion. 16 Thus, the higher degree of bacterial attachment, as well as the enhanced corrosion, may lead to more changes on the SLA titanium surface, including roughness and wettability.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, cigarette‐smoking also includes a state of oxidative stress in bodily tissues including oral epithelial cells . Furthermore, from a microbial perspective, it is hypothesized that pathogenic bacteria that are associated with the etiopathogenesis pf peri‐implant diseases in patients with conventionally‐loaded SDIs (such as Porphyromonas gingivalis and Aggregatibacter Actinomycetemcomitans ) are also associated the etiology of peri‐implant diseases in patients with immediately‐loaded NDIs . Additional studies therefore warranted to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregatibacter Actinomycetemcomitans) are also associated the etiology of peri-implant diseases in patients with immediately-loaded NDIs. 32,33 Additional studies therefore warranted to test these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…The titanium disks were exposed to human saliva in order to reproduce the physiological protein layer known to mediate bacterial adhesion on the implant surface in vivo. Disks with moderate surface roughness (S a :1.30 µm) were used as 95% of the surfaces in currently commercialized implant systems are composed of titanium with a moderately rough topography [15], and the greater affinity of bacteria and peri-implantitis progression for this type of surfaces is well-known [16,17].…”
Section: Discussionmentioning
confidence: 99%